An averaged approach to asperity contact interactions for non-gaussian lubricated surfaces - Michael Leighton; Nick Morris; Ramin Rahmani; Homer Rahnejat (2015)
An averaged approach to asperity contact interactions for non-gaussian lubricated surfaces